Global, regional, and national burden of upper respiratory infections and otitis media, 1990–2021: a systematic analysis from the Global Burden of Disease Study 2021 - Sirota, Sarah Brooke (2024)
Background: Upper respiratory infections (URIs) are the leading cause of acute disease incidence worldwide and contribute to a substantial health-care burden. Although acute otitis media is a common complication of URIs, the combined global burden of URIs and otitis media has not been studied comprehensively. We used results from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021 to explore the fatal and non-fatal burden of the two diseases across all age groups, including a granular analysis of children younger than 5 years, in 204 countries and territories from 1990 to 2021. Methods: Mortality due to URIs and otitis media was estimated with use of vital registration and sample-based vital registration data, which are used as inputs to the Cause of Death Ensemble model to separately model URIs and otitis media mortality by age and sex. Morbidity was modelled with a Bayesian meta-regression tool using data from published studies identified via systematic reviews, population-based survey data, and cause-specific URI and otitis media mortality estimates. Additionally, we assessed and compared the burden of otitis media as it relates to URIs and examined the collective burden and contributing risk factors of both diseases. Findings: The global number of new episodes of URIs was 12·8 billion (95% uncertainty interval 11·4 to 14·5) for all ages across males and females in 2021. The global all-age incidence rate of URIs decreased by 10·1% (–12·0 to –8·1) from 1990 to 2019. From 2019 to 2021, the global all-age incidence rate fell by 0·5% (–0·8 to –0·1). Globally, the incidence rate of URIs was 162 484·8 per 100 000 population (144 834·0 to 183 289·4) in 2021, a decrease of 10·5% (–12·4 to –8·4) from 1990, when the incidence rate was 181 552·5 per 100 000 population (160 827·4 to 206 214·7). The highest incidence rates of URIs were seen in children younger than 2 years in 2021, and the largest number of episodes was in children aged 5–9 years. The number of new episodes of otitis media globally for all ages was 391 million (292 to 525) in 2021. The global incidence rate of otitis media was 4958·9 per 100 000 (3705·4 to 6658·6) in 2021, a decrease of 16·3% (–18·1 to –14·0) from 1990, when the incidence rate was 5925·5 per 100 000 (4371·8 to 8097·9). The incidence rate of otitis media in 2021 was highest in children younger than 2 years, and the largest number of episodes was in children aged 2–4 years. The mortality rate of URIs in 2021 was 0·2 per 100 000 (0·1 to 0·5), a decrease of 64·2% (–84·6 to –43·4) from 1990, when the mortality rate was 0·7 per 100 000 (0·2 to 1·1). In both 1990 and 2021, the mortality rate of otitis media was less than 0·1 per 100 000. Together, the combined burden accounted for by URIs and otitis media in 2021 was 6·86 million (4·24 to 10·4) years lived with disability and 8·16 million (4·99 to 12·0) disability-adjusted life-years (DALYs) for all ages across males and females. Globally, the all-age DALY rate of URIs and otitis media combined in 2021 was 103 per 100 000 (63 to 152). Infants aged 1–5 months had the highest combined DALY rate in 2021 (647 per 100 000 [189 to 1412]), followed by early neonates (aged 0–6 days; 582 per 100 000 [176 to 1297]) and late neonates (aged 7–24 days; 482 per 100 000 [161 to 1052]). Interpretation: The findings of this study highlight the widespread burden posed by URIs and otitis media across all age groups and both sexes. There is a continued need for surveillance, prevention, and management to better understand and reduce the burden associated with URIs and otitis media, and research is needed to assess their impacts on individuals, communities, economies, and health-care systems worldwide. Funding: Bill & Melinda Gates Foundation.